Vegetable Oil-Based Self-Microemulsifying Drug Delivery System of Eprosartan Mesylate: in vitro and ex vivo Evaluation - Bindhani, Sabitri; Mohapatra, Snehamayee; Kumar Kar, Rajat (Asian Journal of Chemistry, 2021)
This study was planned to increase the intestinal permeability and thereby bioavailability of eprosartan mesylate (EPM) by designing a self-microemulsifying drug delivery system (SMEDDS) by the use of vegetable oils. Various SMEDDS-based formulations were prepared with oleic acid and peppermint oil. Tween 80 was used as surfactant and PEG 400 as co-surfactant. Pseudo ternary phase diagrams were constructed for identifying emulsification region between 1:1, 1:2, 2:1, 3:1 ratio of SCOS mix. Eight batches of SMEDDS were found to be thermodynamically stable and from which SMEDDSOF9 and PF5 were best formulations due to their highest drug content, minimum particle size. They have shown highest release of drug in vitro and higher in vitro drug diffusion and ex vivo permeation analysis than pure drug. FTIR study ascertained no incompatibility between drug and excipients present in formulation. From the accelerated stability study, slight effect on particle size and zeta potential, assay content along with cumulative % of drug release was found. The results demonstrated the SMEDDS of EPM are potent drug delivery system to increase dissolution rate and bioavailability of drug via increased intestinal permeability and consequently improving the therapeutic efficacy of eprosartan mesylate.